Cutting path optimization for an automatic cutter in polynomial time using a 3/2 approximation algorithm - Eapen, Neeta A.; Heckendorn, Robert B. (International journal of advanced manufacturing technology, 2021)
The optimal path to be followed by an automatic cutter to cut a set of shapes arranged on a material is termed as the cutting path determination problem. The shapes are often considered as polygons. Each polygon can be either cut entirely (complete cutting approach) or partially (partial cutting approach) before cutting the next polygon. This work solves the cutting path determination problem using the partial cutting approach. The proposed approximation algorithm uses the concepts of ma tching, s panning tree, and tri angulation, and is hence termed as MASTRI. The MASTRI algorithm has a time complexity of O ( n log n ) where n is the total number of vertices of all the polygons. The cutting path computed by the MASTRI algorithm is guaranteed to be within a factor of 3/2 of optimum travel distance of the cutter. No other algorithm has been developed for the partial cutting approach which runs in polynomial time. The MASTRI algorithm is evaluated on 285 input problems, of which 192 problems are randomly generated, and 93 problems are taken from literature. The experimental analysis shows that the MASTRI algorithm computes the cutting path in a very short amount of time. The comparison of MASTRI algorithm with existing works in the literature shows that the MASTRI algorithm gives a shorter cutting path in less time. The MASTRI algorithm can be used for computing cutting path in industries like sheet metal cutting.